2021
DOI: 10.1371/journal.pmed.1003553
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic risk factors for COVID-19 susceptibility and severity: A Mendelian randomization analysis

Abstract: Background Epidemiological studies report associations of diverse cardiometabolic conditions including obesity with COVID-19 illness, but causality has not been established. We sought to evaluate the associations of 17 cardiometabolic traits with COVID-19 susceptibility and severity using 2-sample Mendelian randomization (MR) analyses. Methods and findings We selected genetic variants associated with each exposure, including body mass index (BMI), at p < 5 × 10−8 from genome-wide association studies (GWAS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
102
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(120 citation statements)
references
References 74 publications
13
102
0
1
Order By: Relevance
“…However, gut dysbiosis by various factors has deleterious effects on host health, including the gastrointestinal tract [26] and immune system [27], and metabolic diseases [28]. The F/B ratio is known as a hallmark of obesity, and, interestingly, two recent studies have reported strong evidence for a causal impact of obesity on the susceptibility and severity of COVID-19 [29,30]. However, recent studies have reported no association between the F/B ratio and obesity [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, gut dysbiosis by various factors has deleterious effects on host health, including the gastrointestinal tract [26] and immune system [27], and metabolic diseases [28]. The F/B ratio is known as a hallmark of obesity, and, interestingly, two recent studies have reported strong evidence for a causal impact of obesity on the susceptibility and severity of COVID-19 [29,30]. However, recent studies have reported no association between the F/B ratio and obesity [31].…”
Section: Discussionmentioning
confidence: 99%
“…Further work examining whether measures of central adiposity (i.e., waist or waist to hip ratio) give better estimates of risks of excess (regional) adiposity from COVID-19, would also be useful. Additional genetic data to validate early findings from Leong and colleagues [ 9 ••] would also be valuable, including extending results to differing ethnic groups and to genetic variants linked to measures of body fat distribution. With respect to interventions, it is unlikely that a weight loss trial can be adequately powered or sufficiently large enough to prove benefits of intentional weight loss on COVID-19 risks.…”
Section: Directions For Future Researchmentioning
confidence: 94%
“…Such methods have been used to support higher BMI as a causal risk factor for multiple cardiovascular outcomes (e.g., coronary heart disease, atrial fibrillation and heart failure) [ 8 •], and many other diseases. Using this MR approach, Leong and colleagues related genetics that underpin 17 cardiometabolic traits to risk for COVID-19 outcomes [ 9 ••]. The only statistically positive association was for genes that predict higher BMI—a 14% (95% CI 7 to 21%) higher risk for COVID-19 hospitalisation per every 1kg/m 2 higher BMI level was noted, a risk around twice seen in observational studies.…”
Section: Geneticsmentioning
confidence: 99%
“…The association of obesity-related traits with COVID-19 outcomes has been confirmed by multiple investigations, also including MR analyses that showed putative causal effects of BMI [9,10,11,41,42], WC [9,10], and trunk fat ratio [9]. Some of these previous investigations also have included MVMR analyses that highlighted how the effect of these traits on COVID-19 is independent of several cardiometabolic traits and other known risk factors [43].…”
Section: Discussionmentioning
confidence: 82%